2016
DOI: 10.4236/ajps.2016.77110
|View full text |Cite
|
Sign up to set email alerts
|

Common Mechanism of Lignification of Compression Wood in Conifers and <i>Buxus</i>

Abstract: Woody plants develop a specialized secondary xylem known as reaction wood to enable formation of an ideal shape. Reaction wood in coniferous species is known as compression wood, and that of woody angiosperms as tension wood. However, the genus Buxus which is classified as an angiosperm, forms compression-wood-like reaction wood. We investigated the mechanism of lignification in coniferous compression wood and Buxus reaction wood: 1) Several lignin synthesis genes were upregulated in differentiating reaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Opposite wood of CW has tensile stress values similar or slightly larger than NW. The CW is typically found in gymnosperm species, although it has been also observed in angiosperms such as Buxus [33][34][35] and some primitive angiosperm species [36,37]. Within species, there is a gradient in CW severity, from light CW generating weak compression to severe CW with larger compression.…”
Section: Different Forms Of Mechanically Active Woodsmentioning
confidence: 99%
“…Opposite wood of CW has tensile stress values similar or slightly larger than NW. The CW is typically found in gymnosperm species, although it has been also observed in angiosperms such as Buxus [33][34][35] and some primitive angiosperm species [36,37]. Within species, there is a gradient in CW severity, from light CW generating weak compression to severe CW with larger compression.…”
Section: Different Forms Of Mechanically Active Woodsmentioning
confidence: 99%
“…In Buxus microphylla var. japonica , the PAL gene is up-regulated in RW ( Hiraide et al, 2016 ). In this study, we observed complex changes in lignin synthesis pathway genes, including PAL4 , PAL5 , CAld5H1 , CCoAOMT2 , and PO2 , respectively.…”
Section: Discussionmentioning
confidence: 99%